Genome-Wide Analysis of Alternative Splicing Provides Insights Into Stress Response of the Pacific White Shrimp Litopenaeus vanname - Zhang, Xiaoxi; Yuan, Jianbo; Zhang, Xiaojun; Liu, Chengzhang; Xiang, Jianhai; Li, Fuhua (Frontiers in Genetics, 2019)
Abstract Alternative splicing (AS) can enhance transcript diversity dramatically and play an important role in stress adaptation. Limited researches of AS have been reported in the Pacific white shrimp (Litopenaeus vannamei), which is an important aquaculture species in the world. Here, we performed a genome-wide identification of AS events in L. vannamei based on eight transcriptomes. We identified 38,781 AS events in the shrimp genome and some of them were validated by PCR experiments. These AS events correspond to 9,209 genes, accounting for 36% of protein-coding genes in the shrimp genome. The number of AS events increased after virus or bacteria infection, and low salinity stress. Type 1 AS genes (AS was initially activated) were mainly enriched in substance and energy metabolism, such as carbon metabolism and amino metabolism. However, type 2 AS genes (AS events changed) displayed specific enrichment under different stress challenge. Specifically, type 2 AS genes under biotic stresses were mainly enriched in pathogenic pathway and immune network, and the AS genes under low salinity stress were significantly enriched for betalain biosynthesis. In summary, our study indicates that AS events are complex in shrimp and may be related to stress adaptation. These results will provide valuable resource for functional genomic studies on crustaceans.